BRIDGING THE GAP: ISLAMIC VIEWS ON AI INTEGRATION FOR NIGERIA’S SOCIETAL ISSUES - AYUBA, Jibril Olaniyi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Islam as a religion touches every aspect of man’s life such that the past, present and future occurrences have been scripted in the Qur’an. Hence, the advancement in technology globally which has generated the integration of Artificial Intelligence (AI) in education, religion, economy, health, socio-cultural and a host of others can never be underestimated. AI has now become a veritable tool used in tackling any societal problems without stress. It is against this background that this paper examines the Islamic views on AI integration for addressing Nigeria’s societal issues. In an attempt to do justice to this paper, secondary data were sourced from textbooks, journal articles, seminar papers, and newspapers, among others on the subject matter. The finding of this study shows that Islam supports the integration of AI as one of the technical methods for tackling education, religion and economic issues in Nigeria. The paper concludes that more awareness should be made of the significance and effective integration of AI in addressing the challenges facing the nations.